Implications Of Brics Currency Formation On Indonesia's Economic Sovereignty - Franciscus Budi Iskandar; Giliman Christupa; Yazidil Bustomi; Nazaruddin Lathif; Asmak Ul Hosnah; Farahdinny Siswajanthy; Lindriyani Sjofjan (International Journal of Science and Environment (IJSE), 2025)
The establishment of a BRICS currency by the alliance of Brazil, Russia, India, China, and South Africa aims to reduce reliance on the US dollar in international trade. This new currency is expected to enhance economic stability for BRICS member countries and mitigate exchange rate fluctuation risks. For Indonesia, an open economy highly dependent on international trade, the presence of a BRICS currency could impact national economic sovereignty. This study aims to analyze the potential effects of the BRICS currency on Indonesia's economic sovereignty, particularly in maintaining national economic stability amid changing global financial architecture. This research utilizes a qualitative approach with a descriptive case study to explore the implications of the BRICS currency on Indonesia's economic policy.